Effect of Moringa oleifera Leaf Meal on Haematology of Nellore Lambs (Indian Journal of Animal Production and Management, 2024)
A three months study was conducted on 18 Nellore lambs to evaluate the effect of incorporating  different levels of Moringa oleifera leaf meal (MOLM) on haematological parameters. Nellore lambs  in similar age and uniform conformation were allocated into three groups (T0, T1and T2) with 6 lambs  per treatment using completely randomized block design. The lambs in T0, T1and T2 groups were  offered concentrate feed incorporated with MOLM at 0, 15 and 30% levels, respectively. Blood  samples were collected at the start and end of the study. Haematological study showed no significant  changes except haematocrit which was significantly higher in control group than MOLM  supplemented group. The results also revealed that all erythrocytes and leucocytes indices were  within the normal physiological range.
Keywords: Haematology; Nellore lambs; Moringa oleifera